2008
DOI: 10.1007/s11999-007-0069-3
|View full text |Cite
|
Sign up to set email alerts
|

Total THA in Adult Osteonecrosis Related to Sickle Cell Disease

Abstract: Level IV, therapeutic study. See the Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 50 publications
3
47
1
2
Order By: Relevance
“…42 In our SCD cohort, readmission rates within 30 days after hip surgery were similar to previously reported all-cause readmission rates 51 and most often attributed to painful vaso-occlusive crises. Prior studies have shown suboptimal surgical outcomes in SCD patients undergoing hip surgery for advanced ONFH with complications such as bleeding and infections triggering vaso-occlusive pain crises in the perioperative period.…”
Section: Hip Surgery Outcomessupporting
confidence: 88%
See 1 more Smart Citation
“…42 In our SCD cohort, readmission rates within 30 days after hip surgery were similar to previously reported all-cause readmission rates 51 and most often attributed to painful vaso-occlusive crises. Prior studies have shown suboptimal surgical outcomes in SCD patients undergoing hip surgery for advanced ONFH with complications such as bleeding and infections triggering vaso-occlusive pain crises in the perioperative period.…”
Section: Hip Surgery Outcomessupporting
confidence: 88%
“…Following hip replacement surgery, vaso-occlusive crises and other complications commonly occur. ONFH morbidity has mostly been described in small, crosssectional, single-institution studies, [38][39][40][41][42][43] with findings that might not be generalizable to a larger population of SCD patients. In our novel approach, we built a large SCD cohort from the socioeconomically diverse state of California, using an iterative process based on methods described in other SCD epidemiologic studies.…”
Section: Discussionmentioning
confidence: 99%
“…They found no differences in radiographic survivorship (95 versus 97 %; p=0.6) or HHS (87 versus 88 points; p=0.75) between the cohorts. Hernigou et al [19] retrospectively reviewed 312 cemented (both, cup and stem) arthroplasties performed in patients with ON and sickle cell disease. Following a mean follow-up of 13 years (range, 5 to 25 years), even though medical complications were observed after 85 operations (27 %), the proportion of orthopaedic complications was 13 %.…”
Section: Osteonecrosis and Sickle Cell Diseasementioning
confidence: 99%
“…In advanced osteonecrosis, the disease course will eventually require surgery. Patients with osteonecrosis related to SCD can be severely disabled where hip or shoulder arthroplasty remains the only surgical option for some of these patients [50], where the disease course will eventually require hip or shoulder arthroplasty [51].…”
Section: Side Effectsmentioning
confidence: 99%